Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

You should get -3x-21.

-3x-21=-12

Now try to solve this.

It should be easier.

x-18=-12

right???

Ya.

x=6

Absolute values will always be positive and negative when it comes to equations.

So now it should look like this(-3){-(x+7)}=-12

then both by -11

-3(-x-7)=-12
3x+21=-12
3x=-21-12
3x=-33
x=-11

Yes that's the second answer.

thxs i got my answers you guys are the best

And you're welcome!

yes it is
in order for x=c to be a solution it must satisfy the equation

the first equation was just solved incorrectly

@200205650 you have to plug into the original equation

Okay then never mind. You are right.